Phytochemical composition, antioxidant potential, and enzyme inhibitory properties of Onosma thracica extracts: A comparative study of extraction methods - Mamdouh Alshammari; Cengiz Sarikurkcu; Fevzi Bardakci; Mousa Alreshidi; Mohd Adnan; Riadh Badraoui; Bektas Tepe (PLoS ONE, 2026)
Onosma thracica is a promising natural source of bioactive phenolic compounds, including flavonoids, yet the influence of extraction technique on its chemical profile and biological properties remains unclear. In this study, methanol extracts prepared by maceration (MAC), ultrasound-assisted extraction (UAE), and Soxhlet extraction (SOE) were comparatively investigated in terms of their detailed phenolic composition, antioxidant capacity, enzyme inhibitory activity, and in silico interaction patterns of individual compounds. Among the tested methods, UAE yielded the highest total phenolic content (45.41 mg GAEs/g extract), whereas SOE produced the richest flavonoid content (71.05 mg REs/g extract). LC–ESI–MS/MS analysis showed that luteolin-7-glucoside and apigenin-7-glucoside were the dominant flavonoids, while chlorogenic acid and rosmarinic acid were the major phenolic acids. Biological assays revealed method-dependent differences in activity. UAE was more effective in total antioxidant capacity and reducing power, while SOE showed stronger radical scavenging and metal chelating performance. In enzyme inhibition assays, SOE displayed the strongest acetylcholinesterase inhibition, whereas tyrosinase inhibition was similar across the extracts. Correlation analysis indicated that the observed bioactivities were closely associated with the overall phenolic composition (including flavonoid constituents), particularly with luteolin-7-glucoside and rosmarinic acid. Docking studies showed favorable interactions of apigenin-7-glucoside and luteolin-7-glucoside with human α-amylase, apigenin-7-glucoside and luteolin with acetylcholinesterase, and rosmarinic acid with human tyrosinase-related protein 1, suggesting that these major phenolic constituents may contribute to the observed bioactivities of O. thracica . The results demonstrate that extraction method markedly shapes the phytochemical composition and bioactivity of O. thracica , and they support further work aimed at optimizing its potential pharmacological use.